2019
DOI: 10.21595/jve.2019.20077
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control of a nonlinear suspension with time-delay compensation

Abstract: This paper addresses the challenge of predictive control of a quarter-car nonlinear suspension and low controller-precision. This is done by designing and implementing an adaptive controller with time-delay compensation. First, a real-time control model is created. Then, time-delay compensation is realized and both frequency-domain and time-domain simulation of the controller performance are conducted. According to the simulation results, the sprung-mass acceleration of the suspension controlled by an adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…There is a vast amount of literature showing the occurrence of such undesired resonances. 3033 Therefore, a novel MIMO fuzzy logic controller is designed in this study as reported above. Figure 11 proves that the fuzzy MBAC shows a significant achievement in reduction of the magnitudes throughout the frequency responses with no undesired resonances.…”
Section: Results and Verification Of Controller Actionmentioning
confidence: 99%
“…There is a vast amount of literature showing the occurrence of such undesired resonances. 3033 Therefore, a novel MIMO fuzzy logic controller is designed in this study as reported above. Figure 11 proves that the fuzzy MBAC shows a significant achievement in reduction of the magnitudes throughout the frequency responses with no undesired resonances.…”
Section: Results and Verification Of Controller Actionmentioning
confidence: 99%
“…Since the same control rate gain matrix is coupled to two different Lyapunov matrices X 1 and X 2 , the feedback gain cannot be directly calculated by inequalities (19)(20)(21)(22).…”
Section: Taylor Series-h 2 /H ∞ Control Strategymentioning
confidence: 99%
“…Recently, the robust control theorem has been widely applied to overcome the active suspension performance degradation caused by the time delay. Bououden et al [19] designed a robust model predictive control based on the Lyapunov–Krasovskii functional method for active suspension systems with time‐varying delays and input constraints, and the state feedback control law was calculated by solving an optimization problem using linear matrix inequality (LMI) terms. In addition, Sun et al [20] studied a finite frequency controller for an active suspension system actuator with an input delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation